Different alkali metals promoted Cr/Al2O3 catalysts for propane dehydrogenation. (15th June 2023) - Fu, Haoyue; Qian, Weixin; Zhang, Haitao; Ma, Hongfang; Ying, Weiyong
Graphical abstract: Highlights: The promoting effects of Li, Na and K doped on Cr/Al2 O3 catalyst are investigated. The doped alkali metal promotes the formation of Cr 6+ species and decreases the amount of acid sites. The initial propane conversion on Cr-0.5Na/Al2 O3 catalyst is 13.7% higher than that of Cr/Al2 O3 catalyst. The carbon deposition on Cr-0.5Na/Al2 O3 catalyst is the lowest. Abstract: Unmodified Cr/Al2 O3 and Cr/Al2 O3 doping with different alkali metals (Li, Na, K) were prepared by the incipient wetness impregnation method. The surface elements of all the catalysts are evenly distributed and well loaded, and the addition of alkali metals does not change the crystal structure and surface texture. Both Cr 6+ and Cr 3+ species exist on all catalysts, and the addition of alkali metals can increase the amount of Cr 6+ species, and Cr 6+ species are basically converted into active Cr 3+ species in the reaction thus increasing the initial propane conversion in the reaction. The addition of alkali metals reduced the amount of total acid sites and the strong acid sites of the catalyst, thus inhibiting the occurrence of side reactions and the formation of carbon deposition, and reducing the deactivation rate of the catalyst. Cr-0.5Na/Al2 O3 exhibited the best catalytic performance and the lowest carbon deposition.